PENGGUNAAN FACEBOOK SEBAGAI MEDIA KOMUNIKASI PEMASARAN KAIN TENUN SONGKET SILUNGKANG - Marta, Revi (Masyarakat Telematika Dan Informasi : Jurnal Penelitian Teknologi Informasi dan Komunikasi, 2015)
Songket weaving well-known by the public for its unique design, sparkling yarn, and high qualities. Songket weaving is not only a result of Minangkabau society, but it is a part of traditional costume as a social function in society. Each region has different patterns which can be seen from the threads it used, design and materials that used. In West Sumatra there are two region that known for their weaving, which is Pandai Sikek and Silungkang. Silungkang is the name of a village located in Sawahlunto city, located on the edge of the causeway of Sumatera. Until now Silungkang weaving is one of the top choices of consumers and suppliers, this success can not be separated from governmentâs role in promoting Sawahlunto city as one of crafting area. Promotion can not be separated from its communication strategy, in this case the communication strategy done by Sawahlunto Public Relation. The communication strategy describes the media selection in delivering the message. The message will be effective if the selected media is also effective, and work for worth communicate.Sawahluntoâs government public relation been using new media as a media to promote Silungkang weaving. One of the new media used is Facebook, by using new media show Sawahlunto seriousness in realizing the cultural tourism concept of Sawahlunto. New media is a new form of social media used by the public, now that conventional media less effective in conveying the messages massively. Article discusses of how the use of new media can help the city government in promoting the activities, policies, and creative industry products to the public.